CHARACTERIZATION OF ELDERLY IN AN INTERNAL UNITY IN INTENSIVE CARE OF A PUBLIC HOSPITAL IN NATAL/ RN (Fiep Bulletin - online, 2013)
The average age of patients in ICU has increased in recent years and will further increase with the aging of the general population. This scenario justifies the concern not only with the human-technological support to the elderly severe, but also with the economic management and the real effectiveness of intensive support in this population. Aiming to characterize elderly patients admitted to the ICU of a public hospital in Natal / RN, as the most common diseases, the length of stay and its evolution. This is a documentary study descriptive and exploratory, with quantitative approach and retrospective data obtained from records of patients admitted to a general ICU of Natal / RN. Data collection was performed during the period from June 2007 to June 2008, through a structured form during the admission and clinical course of patients. It was a female predominance of elderly hospitalized (51.2%), where 51% were aged between 75 to 84 years, the most common length of hospital stay was 1 to 7 days (81.4%), we obtained in 60.5% of cases as high clinical outcome, and the clinical diagnoses were present more cardiovascular disorders (34.9%), distributed between the diagnosis of congestive heart failure (CHF), coronary artery disease (CO), of acute myocardial infarction (MI), angina, acute lung edema (EAP) and hypertension (SH). We conclude that the increase of life expectancy of the population and the development of chronic diseases, have influenced the increase in admissions of elderly patients in ICU. In this sense, it is necessary a better reflection of the care given to this population, aiming at the prevention of diseases and reduce hospitalizations, as the comorbidities, cognitive function, the functional status and care will become integral components of fundamental importance and a challenge to the nurse in assisting the elderly hospitalized in ICU.
Keywords: Hospitalization; Elderly; Intensive Care Unit; Nursing